Islamic Banking Students Experiences with Mobile-Based Vocabulary Applications in Learning English for Sharia Finance - Aulia Rahman; Siti Nurhasanah (EXPOSE (Journal of English Education and for Specific Purpose), 2025)
The increasing globalization of the Islamic finance industry has intensified the need for Islamic banking graduates to possess adequate English proficiency, particularly in mastering specialized sharia banking vocabulary. This study aims to investigate students perceptions and learning experiences regarding the use of mobile-based vocabulary applications in the English for Sharia Banking course. To address this aim, a sequential explanatory mixed-method design was employed to obtain both numerical trends and in-depth experiential insights. The quantitative phase involved 58 students from the Islamic Banking Study Program at STIES Mitra Karya, Bekasi, selected through purposive sampling. Data were collected using a Likert-scale questionnaire consisting of six indicators: ease of use, learning flexibility, motivation, vocabulary mastery, learner autonomy, and relevance to Islamic banking contexts. Descriptive statistical analysis revealed that learning flexibility obtained the highest mean score (M = 4.32), followed by vocabulary mastery (M = 4.28) and learner autonomy (M = 4.21), indicating strong student agreement on the benefits of mobile-based vocabulary learning. Ease of use (M = 4.15), motivation (M = 4.18), and relevance to sharia banking (M = 4.24) also received positive evaluations. The qualitative phase involved semi-structured interviews with six participants and was analyzed thematically. The findings indicate that mobile applications, particularly Quizlet and Wordwall, support vocabulary retention through repetitive quizzes and interactive features, increasing students motivation and independent learning. However, qualitative data also reveal limitations in contextual and productive vocabulary use, as students reported difficulties applying Islamic banking terms in sentences and professional communication. In conclusion, mobile-based vocabulary applications are effective supplementary tools for enhancing vocabulary recognition and retention in English for Sharia Banking courses. Nevertheless, these tools should be integrated with contextualized learning activities to support communicative competence in sharia banking contexts.